The role of diet on intestinal microbiota metabolism: Downstream impacts on host immune function and health, and therapeutic implications - Goldsmith, Jason R (2014)
Dietary impacts on health may be one of the oldest concepts in medicine; however, only in recent years have technical advances in mass spectroscopy, gnotobiology, and bacterial sequencing enabled our understanding of human physiology to progress to the point where we can begin to understand how individual dietary components can affect specific illnesses. This review explores the current understanding of the complex interplay between dietary factors and the host microbiome, concentrating on the downstream implications on host immune function and the pathogenesis of disease. We discuss the influence of the gut microbiome on body habitus and explore the primary and secondary effects of diet on enteric microbial community structure. We address the impact of consumption of non-digestible polysaccharides (prebiotics and fiber), choline, carnitine, iron, and fats on host health as mediated by the enteric microbiome. Disease processes emphasized include nonalcoholic fatty liver disease (NAFLD)/non-alcoholic steatohepatitis (NASH), IBD, and cardiovascular disease (CVD)/atherosclerosis. The concepts presented in this review have important clinical implications, although more work needs to be done to fully develop and validate potential therapeutic approaches. Specific dietary interventions offer exciting potential for nontoxic, physiologic ways to alter enteric microbial structure and metabolism to benefit the natural history of many intestinal and systemic disorders.